The BP Gulf of Mexico oil spill. Part 3 - Crandall, William, 1956- (SAGE knowledge. Cases., 2016)
On April 20, 2010, BP's offshore drilling rig, the Deepwater Horizon, exploded in the Gulf of Mexico and caused the largest accidental marine oil spill in history. This case examines the tragic effects of the accident and sheds light on the reasons that caused it.